Effect of Bombyx mori silk-fiber volume on flexural strength of fiber-reinforced composite - Aria Fransiska; Siti Sunarintyas; Rini Dharmastiti (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Dental glass fiber is one of dental synthetic fibers that are widely used in dentistry as a dental resin reinforcement, such as in dentin replacement material. The availability of glass fiber is limited in Indonesia because it must be imported and relatively expensive. Bombyx mori silk-fiber is one of the strongest natural fiber derived from silkworm cocoon processing. Silk-fiber is used in medical applications as a post-surgical sutures, scaffolds for tissue engineering and drug delivery. The purpose of this study was to evaluate the effect of Bombyx mori silk-fiber volume on the flexural strength of fiber-reinforced composite (FRC). We used Bombyx mori silk-fiber (Perhutani Pati, Central Java, Indonesia) and flowable composite (Charmfil flow, Denkist, Korea) in this study. The FRC samples were divided into 4 groups consisting of fiber volumes of 0%, 5%, 10% and 15% (n = 4). Tests of flexural strength were performed according to ISO 4049. The results were analyzed using one way ANOVA (p<0.05). The study showed that the means of the flexural strength (MPa) of Bombyx mori silk-fiber FRC for volume of 0%, 5%, 10% and 15% were 149.2 ± 5.5; 127.6 ± 3.8; 110.9 ± 3.5; 71.2 ± 4.2. One-way ANOVA test showed that the means of FRC flexural strength on the four groups’ silk-fiber Bombyx mori volumetric were significantly different (p<0.05). This study concluded that Bombyx mori silk-fiber volumetric influences the flexural strength of fiber- reinforced composite. An increase in Bombyx mori silk-fiber volume decreases the flexural strength of FRC because there is a small gap due to the weak interfacial bonds between dental flowable composite and Bombyx mori silk-silk-fiber.